Hormesis and a Chemical Raison D'ětre for Secondary Plant Metabolites - Franz Hadacek; Gert Bachmann; Doris Engelmeier; Vladimir Chobot (SAGE Publishing, 2011)
In plants, accumulation in specific compartments and huge structural diversity of secondary metabolites is one trait that is not understood yet. By exploring the diverse abiotic and biotic interactions of plants above- and belowground, we provide examples that are characterized by nonlinear effects of the secondary metabolites. We propose that redox chemistry, specifically the reduction of reactive oxygen species (ROS) and, in their absence, reduction of molecular oxygen by the identical secondary metabolite, is an important component of the hormetic effects caused by these compounds. This is illustrated for selected phenols, terpenoids, and alkaloids. The redox reactions are modulated by the variable availability of transition metals that serve as donors of electrons in a Fenton reaction mode. Low levels of ROS stimulate growth, cell differentiation, and stress resistance; high levels induce programmed cell death. We propose that provision of molecules that can participate in this redox chemistry is the raison d'ětre for secondary metabolites. In this context, the presence or absence of functional groups in the molecule is more essential than the whole structure. Accordingly, there exist no constraints that limit structural diversity. Redox chemistry is ubiquitous, from the atmosphere to the soil.